2013
DOI: 10.5194/acp-13-9819-2013
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic properties of smoke-generated organic aerosol particles emitted in the marine atmosphere

Abstract: Abstract. During the Eastern Pacific Emitted Aerosol CloudExperiment (E-PEACE), a plume of organic aerosol was produced by a smoke generator and emitted into the marine atmosphere from aboard the R/V Point Sur. In this study, the hygroscopic properties and the chemical composition of the plume were studied at plume ages between 0 and 4 h in different meteorological conditions. In sunny conditions, the plume particles had very low hygroscopic growth factors (GFs): between 1.05 and 1.09 for 30 nm and between 1.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…These results are consistent with recently published work [18,64] that shows SOMA as a significant contributor to CCN activity in marine regions. Finally, all samples display similar droplet growth kinetics to CCN composed of (NH4)2SO4, suggesting that water-soluble organics do not significantly impact the growth rate of CCN.…”
Section: Summary and Implicationssupporting
confidence: 83%
“…These results are consistent with recently published work [18,64] that shows SOMA as a significant contributor to CCN activity in marine regions. Finally, all samples display similar droplet growth kinetics to CCN composed of (NH4)2SO4, suggesting that water-soluble organics do not significantly impact the growth rate of CCN.…”
Section: Summary and Implicationssupporting
confidence: 83%
“…For example, Ruehl et al [] have shown that products from α ‐pinene ozonolysis reduce the surface tension of NaCl particles by 50–75%, implying that surface active products may enhance water uptake in certain aerosols. Wonaschütz et al [] found that in the study region examined here, initially hydrophobic organics emitted from an ocean vessel yielded higher CCN after atmospheric aging.…”
Section: Resultsmentioning
confidence: 81%
“…A bulk hygroscopicity parameter (κ) is derived using the method of Petters and Kreidenweis (2007) and by assuming total activation above a critical activation diameter, such that the CCN concentration exactly matches the concentration of particles exceeding this critical diameter (Furutani et al, 2008; Burkart et al, 2011; Wonaschütz et al, 2013). Hygroscopicity decreases concurrently with the morning traffic signature (Fig.…”
Section: Climatological Resultsmentioning
confidence: 99%